Mechanics of tillage implements - Ahmad, Desa (Universiti Putra Malaysia Press, 2009)
Tillage operations are especially consumptive of energy. The consumption of energy as well as the wear and tear of tractors and implements increase sharply with working depth. The traditional and still widely practiced tillage system is based on a series of primary cultivations, aimed at breaking the soil mass into a loose system of clods of mixed sizes, followed by secondary cultivation aimed at pulverization, repacking and smoothening of the soil surface. These practices which are performed uniformly over the entire field often involve a whole series of successive operations each of which is necessary to correct or supplement the previous operation, all at the cost of energy and water usage in the case of paddy fields. Existing information on tillage of wet soils reveals that equipment and timing of operations vary with location, soil type and availability of irrigation water and power. Water usage and energy requirements are high due to the increased number of operations. Whilst much work has been documented on the agronomy, breeding, insect and disease control of rice, there is limited research recorded on optimum water levels and the most efficient implement which creates the disturbance required. Although well prepared mud is favourable, experiments to establish the optimum moisture content to obtain such a condition are lacking. This lack of a quantitative description of the degree of puddling poses a major hindrance in performance evaluation of puddling equipment and this in turn hampers the improvement of implement design. The difficulty in quantifying the degree of change in the structure of soil brought about by wetland tillage best suited to the requirement of the rice plant, stems from the fact that very little work has been done to relate the optimum condition to the maximum yield or growth obtained. This paper focuses on the basic tillage implement requirements for wet soil conditions for both upland and lowland cropping systems based on soil behaviour at higher moisture content. Basic cultivation operations and the types of soil disturbance needed for each are identified. Soil and implement factors influencing draught and power requirements are considered and the action and type of soil disturbance caused by the different implement types are described. A method for choosing the basic implement types necessary for specific field situations is suggested and appropriate tools and techniques are recommended. Implement designs and energy requirements for dry soil conditions are discussed for comparison. Estimation of energy requirements using predictive models based on the Mohr-Coulomb soil mechanics theory is also presented.